2002
DOI: 10.1146/annurev.physiol.64.081501.155847
|View full text |Cite
|
Sign up to set email alerts
|

Human and Murine Phenotypes Associated with Defects in Cation-Chloride Cotransport

Abstract: The diuretic-sensitive cotransport of cations with chloride is mediated by the cation-chloride cotransporters, a large gene family encompassing a total of seven Na-Cl, Na-K-2Cl, and K-Cl cotransporters, in addition to two related transporters of unknown function. The cation-chloride cotransporters perform a wide variety of physiological roles and differ dramatically in patterns of tissue expression and cellular localization. The renal-specific Na-Cl cotransporter (NCC) and Na-K-2Cl cotransporter (NKCC2) are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
139
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(140 citation statements)
references
References 230 publications
1
139
0
Order By: Relevance
“…NKCC1 is expressed in secretory epithelia, including trachea, salivary glands, and inner ear. In these tissues, it is localized in the basolateral membrane and takes up ions to support chloride secretion by apical chloride channels into the lumen of these tissues (27,28). NKCC1 is ubiquitously expressed in nonepithelial tissues, such as cardiac cells and fibroblasts, and influences volume regulation and ion balance through its sensitivity to changes in osmotic stress, intracellular chloride, and, directly or indirectly, cell volume.…”
Section: Discussionmentioning
confidence: 99%
“…NKCC1 is expressed in secretory epithelia, including trachea, salivary glands, and inner ear. In these tissues, it is localized in the basolateral membrane and takes up ions to support chloride secretion by apical chloride channels into the lumen of these tissues (27,28). NKCC1 is ubiquitously expressed in nonepithelial tissues, such as cardiac cells and fibroblasts, and influences volume regulation and ion balance through its sensitivity to changes in osmotic stress, intracellular chloride, and, directly or indirectly, cell volume.…”
Section: Discussionmentioning
confidence: 99%
“…As it has been proposed that SLC12A6 resembles a positional candidate gene for bipolar disorder and subtypes of schizophrenia (Delpire and Mount, 2002;Meyer et al, 2005), we investigated whether the SLC12A6 polymorphic promoter sites are prone to stimulation by common mood stabilizers, such as Li and valproic acid, which are both commonly used in the treatment of bipolar disorder, and the antipsychotic drug haloperidol, frequently used in the treatment of psychoses. However, presence of haloperidol, valproic acid, or Li had no effect on reporter gene expression in our test system, as they also had no influence on promoter methylation (data not shown).…”
Section: Effects Of Mood Stabilizers and Antipsychotic Drugs On Cpg Mmentioning
confidence: 99%
“…Na + -K + -Cl À cotransporter isoform 1 (NKCC1) has a broad tissue distribution, whereas NKCC2 is found only in the vertebrate kidney (Delpire and Mount, 2002). NKCC serves multiple functions, including ion and fluid movements in secreting or reabsorbing epithelia and cell volume regulation (Delpire and Mount, 2002;Russell, 2000). We reported that NKCC1 activity, reflected by protein phosphorylation, is increased in the cortex and striatum during 0 to 8 h reperfusion after 2-h transient middle cerebral artery occlusion in rat (tMCAO, Yan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%